GAMBARAN KESEHATAN MENTAL LANSIA DI POSBINDU UPTD PKM BUNGURSARI - Suci Hardianti; Wirdan Fauzi Rahman; Sindy, Sindy (Bajang Institute, 2025)
Adolescent mental health is a crucial aspect of individual development, yet it is often overlooked. The purpose of this study is to provide an overview of the mental health issues of the elderly at the Integrated Health Service Post (Posbindu) of the Bungursari Community Empowerment and Family Welfare Development Center (UPTD PKM) in Purwakarta City, and the factors that influence them. The method used was descriptive with a quantitative approach, through data collection using questionnaires completed by the elderly. Based on the study results, the majority of elderly people experience anxiety and depression, with the main influencing factors being changes in mental well-being, such as stress, anxiety, loneliness, and depression. Poor mental health can negatively impact the quality of life and physical health of the elderly. Therefore, understanding the mental health of the elderly is crucial as a basis for planning promotive and preventive interventions in the community.